Aplicación del proceso de atención de enfermería en un recién nacido a termino con ictericia fisiológica del área de neonatología del Hospital General Guasmo Sur - Guerrero Blum, Grace Daniela (2020)
Jaundice is shown as a yellow dye in skin and mucous membranes produced by the storage of bilirubin. Attention is given to the neonate when serum bilirubin is high enough, it is related to hyperbilirubinemia with elevated serum values at 46 mg / dL of total bilirubin. Physiological jaundice is a very common scenario in the term neonate described as being monosymptomatic, it is assumed as physiological levels up to 10 mg of bilirubinemia in the term newborn the peak occurs between 72-120 hours and is resolved between 7 -10 days. The current case study aims to expose and execute the nursing care process that should be dedicated to newborns at the end with physiological jaundice based on the theoretical basis of nursing and especially on the principles of nursing such as: humanism, offer a service with quality, warmth and efficiency. This will allow us to find out and prevail the health needs and / or problems that the newborn presents at term by means of the timely identification of nursing diagnoses and the application of nursing care in an integral way, thus achieving its speedy recovery and well-being. This case study is aimed at enhancing the level of knowledge of society in order to reduce the rate of newborns to terms that show physiological jaundice due to some of the causes already mentioned above.